Triply Exploited: Female Victims of Smuggling and Trafficking Networks Strategies for Pursuing Protection and Legal Status in Countries of Destination - Anna Marie Gallagher (Deusto Journal of Human Rights, 2017)
Although efforts have been directed towards the protection of victims of human trafficking and smuggling, the existing systems are still flawed and lack more effective ways to provide support, assistance and long-term status to those victims. Several international mechanisms exist, however, the protection and assistance they provide often depends on the nature or value of the information provided by victims. Asylum may be the only relief available to victims of smuggling, many of whom suffer serious human rights violations. This article provides several proposals for obtaining permanent legal status in destination countries for women who fear returning to their home country or who cannot return because of great economic need. Specifically, the article will discuss relief under the 1951 Convention Relating to the Status of Refugees and the 1967 Protocol, provide suggestions for improved trafficking visas and, finally, suggest that labour based immigration include work visas for prostitutes. Published online: 11 December 2017